Improving Students’ Reading Comprehension Through KWL (Know-Want-Learn) Strategy: (A classroom action research at Eighth Grade Students of SMP Islam Al-Asmaniyah) - Aris Setyawan (STAI Asy-Syukriyyah, 2018)
This research basically is conducted to improve students’ reading comprehension through KWL (Know, What, to learn) at the eight grade of SMP Islam Al-Asmaniyah. This research had been done at eigth grade of SMP Islam Al-Asmaniyah located Kab. Tangerang, Banten. This research had been taken in semester II. It had done since April 2018 – June 2018 in academic year 2017 – 2018. This research is classroom action research with qualitative approach. As for design classroom action research which is used in this study is to use a model of Kemmis and McTaggart that used 3 cycles where each cycle included planing, acting, observing, and reflecting. The result of reading test in cycle I using KWL got the average score of 71,8 where there are 59 % students that got KKM. In cycle II, the result of reading test using KWL got the average score of 76 where there are 76% students that got KKM. The students were easier to read the text given. Although they still found difficult in understanding the text because of the limitation of their vocabulary. The result of reading test got better in cycle III. The students were more understand in doing their activity in KWL and more active in learning. In this cycle, they got the average score of 83,2 where there are 93% students that got KKM. KWL can be considered as an effective way to improve students’ achievement in reading comprehension.